Nanoparticle-based combination of LMWH and doxorubicin for the efficient treatment of hepatocellular carcinoma with portal vein tumor thrombus. (April 2023) - Zhang, Xiu-Ping; Li, Bozhao; Lu, Zefang; Hu, Ming-Gen; Zhao, Guo-Dong; Xu, Shuai; Wu, Zhouliang; Chu, Tianjiao; Qi, Feilong; Wu, Suying; Nie, Guangjun; Li, Suping; et al.
Abstract: Portal vein tumor thrombus (PVTT) is an important indicator of advanced hepatocellular carcinoma (HCC) with poor prognosis; however, there currently is no effective treatment paradigm for PVTT to improve the therapeutic efficacy of advanced HCC. Here we demonstrate that PVTT largely comprises a mixed composition of thrombosis and tumor cells, and in this case develop an acid-responsive polymeric nanocarrier that codelivered anticoagulant and chemotherapeutic drug into PVTT to achieve effective inhibition of HCC tumors. The anticoagulant, low molecular weight heparin (LMWH), was loaded to degrade thrombus layer to expose tumor cells of HCC tissues to chemotherapeutic doxorubicin (Dox). The killing effect of tumor cells by Dox was expected to decrease fibronectin deposition leading to PVTT degradation, and thus relieving portal hypertension. This PVTT-targeted nanocarrier enabled a PVTT-localized, continuous accumulation of the two drugs at a constant ratio. In both subcutaneous and orthotopic mouse models of PVTT, the nanoparticle-based strategy achieved potent anti-tumor efficacy without harsh side effects. This work uncovers the central need for PVTT modulation in advanced HCC treatment and represents a promising strategy for treating tumors accompanied by hypercoagulability and vascular invasion. Graphical Abstract: ga1 Highlights: PVTT is an important indicator of advanced HCC with poor prognosis. A PVTT-targeted, acid-responsive PHPC-D-L nanodrug codelivered LMWH and DOX into PVTT to achieve effective inhibition of HCC tumors and relieving portal hypertension. This work offered a promising strategy for treating tumors accompanied by hypercoagulability and vascular invasion.